Herbal Medicine for Burns Injury: A Narrative Literature Review - Yufimar Riza Fadilah (Open Access Indonesian Journal of Medical Reviews, 2021)
Traditional medicine uses various phytochemicals for wound healing, supplying enhanced healing processes via anti-inflammatory or antioxidant activity. This literature review aimed to describe herbal medicine for burn injuries. The main stages of the recovery process for burned skin include the migration of blood cells from deep within the burn wound, the promotion of local inflammation, the removal of cellular debris and pathogens, the proliferation of connective tissue and extracellular matrix, the neovascular network (angiogenesis) and tissue remodeling. Therefore, the ideal medicine for burn patients should have excellent wound healing potential and show positive effects at different stages of wound repair. The antioxidant activity is a good option for treating burns. Topical antimicrobial therapy is one of the most essential methods of burn wound care. The ideal antibacterial agent for wound infection prevention and control should directly kill pathogens and reduce local inflammation and tissue destruction. Therefore, herbal products can be used successfully to treat wounds. In conclusion, herbal medicine is recommended to conduct advanced clinical and pharmaceutical research to produce new natural medicines for treating burn wounds.